Sources of psychological stresses among a sample parents of children with disabilities in Lattakia - شروف, أنساب; محمد, هلا (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The current research aimed to identify sources of psychological stresses among a sample parents of children with disabilities in Lattakia. The research aimed too to identify the level of psychological stresses of the random. The sample was drawn using a satisfied random method from the rehabilitation centers for peoples with disabilities. These centers affiliated to the directorate of social affair . The sample included (62) individual : (38 mothers t and 24 fathers). In order to achieve the research objectives, a scale of psychological stress measure for Sartawi and Shahes was used. The results showed that the most sources of psychological stresses were the sources related to the child independent performances, then sources related to the parents concern the child future, then sources related to the family and the support of partner, while the sources of cognitive problems came at the end. The results indicated that the most of random has a middle level of psychological stress, there were also no differences between fathers and mothers in degree of psychological stress, neither according to type of handicap.